Energy from organic sources - Mohd Noor, Warda Hanani; Mohmad Jaat, Norrizam; Khalid, Amir; Leman, Abdul Mutalib; Mohamed Sunar, Norshuhaila (Penerbit UTHM, 2020)
Elevated environmental awareness and exhaustion of resources are leading to develop substitute fuel from renewable resources that can be environmentally friendly. Bio-diesel fuel is a substitute to petrol base fuels currently being obtained from vegetable oils, animal fat, utilized oils from restaurants etc. Pet animal fats represent large wastes in tanneries. With a high energetically worth, animal fats may make up an energetical source with significant capital opportunities as raw substance (used with high precautionary measure) or also as oils acquired from ester interchange with alcohol (biodiesel) with higher facets being used as fuel at diesel engines.